A Pilot Study of Nutritional Status Prior to Bariatric Surgery in South China - Sun, Linli; Wang, Chunxia; Sun, Wei; Wang, Chunjiang (Frontiers in Nutrition, 2021)
Objective: The was a pilot study to assess the biochemical and historical information about bariatric patients before undergoing the surgery in the aim of identifying nutritional deficiencies and their prevalence from 2015 to 2020. Methods: Clinical data of 247 patients (105 males and 142 females) were included. Vitamins, trace elements, electrolytes, albumin, globulin, hemoglobin, folate, ferritin, microalbuminuria (MAU), and parathyroid hormone (PTH) levels were determined to explore the nutritional status according to gender, age, high body mass index (BMI) and waist circumstance (WC). Results: The mean age, mean BMI and mean WC of the candidates were 32.95±10.46 years, 38.01±7.11 kg/m2, and 117.04±16.18 cm, respectively. The prevalence of preoperative nutritional deficiencies was 76.88% for 25OH vitamin D, 19.84% for globulin, 11.74% for albumin, 11.02% for sodium, 8.33% for folic acid, 7.69% for chloride, 4.05% for calcium, 2.36% for ferritin, 11.90% for elevated PTH and 44.96% for MAU. Males exhibited increased prevalence of globulin and MAU relative to females (P＜0.05). Older groups are more likely to exhibit albumin deficiency (P = 0.007), globulin deficiency (P = 0.003), and zinc deficiency (P = 0.015). In addition, 25 (OH) D deficiency and albumin deficiency were more common in patients with BMI ≥ 47.5 kg/m2 (P = 0.049 and P = 0.015, respectively). Wider WC (≥ 150 cm) exhibited higher rates of albumin deficiencies (P = 0.011). Conclusion: Electrolyte and nutritional deficiencies were common in patients prior to bariatric surgery in South China. Routine evaluation of electrolyte and nutritional levels should be carried out in this population.